THE CONDITIONS OF AN ACTIVE EQUATORIAL GSS ENTERING THE EARTH’S SHADOW - Karpenko, G. F.; Murnikov, B. A.; Suhov, P. P. (Одеські астрономічні публікації, 2009)
In this article we describe the conditions of an active GSS entry and exit from the Earth’s shadow relative to the plane of the Earth’s equator with a small inclination of the orbit to the equator.